The Effect of Endolymphatic Hydrops and Mannitol Dehydration Treatment on Guinea Pigs - Wang, Shu-Qi; Li, Chen-Long; Xu, Jing-Qi; Chen, Li-Li; Xie, You-Zhou; Dai, Pei-Dong; Ren, Liu-Jie; Yao, Wen-Juan; Zhang, Tian-Yu (Frontiers in Cellular Neuroscience, 2022)
Background Endolymphatic hydrops (EH) is considered as the pathological correlate of Menière’s disease (MD) and cause of hearing loss. The mechanism of EH, remaining unrevealed, poses challenges for formalized clinical trials. Objective This study aims to investigate the development of hearing loss, as well as the effect of dehydration treatment on EH animal models. Methods In this study, different severity EH animal models were created. The laser Doppler vibrometer (LDV) and auditory brainstem responses (ABR) were used to study the effects of EH and the dehydration effects of mannitol. The LDV was used to measure the vibration of the round window membrane (RWM) reflecting the changes in inner ear impedance. ABR was used to evaluate the hearing changes. Furthermore, tissue section and scanning electron microscopy (SEM) observations were used to analyze the anatomical change to the cochlea and outer hair cells. Results The RWM vibrations decreased with the severity of EH, indicating an increase in the cochlear impedance. The dehydration therapy lowered the impedance to restore acoustic transduction in EH 10- and 20-day animal models. Simultaneously, the ABR thresholds increased in EH models and were restored after dehydration. Moreover, a difference in the hearing was found between ABR and LDV results in severe EH animal models, and the dehydration therapy was less effective, indicating a sensorineural hearing loss (SNHL). Conclusion Endolymphatic hydrops causes hearing loss by increasing the cochlear impedance in all tested groups, and mannitol dehydration is an effective therapy to restore hearing. However, SNHL occurs for the EH 30-day animal models, limiting the effectiveness of dehydration. Our results suggest the use of dehydrating agents in the early stage of EH.